Silvopastoral system for sustainable cattle production in the tropics of Mexico - Erales Villamil, José Alberto, author; Salman, Mo, advisor; Reid, Robin S., committee member; Solorio Sánchez, Francisco J., committee member; Van Metre, David C., committee member; Zepeda, Cristobal, committee member (Colorado State University. Libraries, 2017)
Traditional production system has exhausted natural resources and depleted soil nutrients reducing farm productivity and forcing farmers to expand farm lands, which, increases deforestation and pollution. Global warming and an increasing global population pose additional strain to the already fragile global food security, making it urgent for innovative production systems to be developed. Such systems, adapted to local circumstances and designed to reduce deforestation and increase food production, must emerge to provide an expanding global food demand while enabling preservation of natural resources. In Mexico, a five-year research project, derived from a national initiative has proposed a silvopastoral model for the Tepalcatepec valley, in the State of Michoacan, as an alternative to conventional livestock ranching in the tropics. The primary objective for this research project was to characterize the advantages and disadvantages of an alternative livestock farming model, the silvopastoral system. One hundred and fifteen farmers in the Tepalcatepec valley were surveyed to characterize their farms, their family demographics, main cattle breed, crops farmed, cattle diet, measures of animal performance (productivity) commercialization (marketing practices) and animal health management practices. An analysis of the progress of the various national SPS initiatives was also performed in order to identify gaps in research, collaboration, stakeholder education, and application of SPS farming in Mexico. A systems analysis was conducted on the research project using the information compiled from the team of scientists surveyed. Components related to carbon capture, biodiversity, soil quality, nutrient recycling, and larger-scale cycles such as water cycle need to be incorporated into future research. An accurate measure of the true economic and ecological impact of SPS farming is an essential goal. Improved communication among scientists, government agencies, and stakeholders is also essential for successful research into SPS farming. The animal health component of the five-year Mexican national SPS project is the focus of this dissertation. Traditional livestock health practices on participating small farms were characterized, and common health problems of cattle were identified. A community based livestock syndromic surveillance system was developed, implemented, and observed for two years on five selected farms. Observations from farmers and veterinarians were triangulated to validate data on animal health collected by laypeople. For each farm under study, monthly cumulative incidence per animal category (calf, grower or adult), the most frequent disease syndrome, and the syndrome that carried the greatest economic impact were calculated. Most Rho correlation coefficients for farmer's and veterinarian's observations were high. Farmers that implemented the silvopastoral model were considered typical of those who practiced this farming method elsewhere within the region. Because participating farms shared production system, husbandry, livestock health status, disease preventive measures, products, and commercialization channels, they were considered an epidemiological compartment for quantitative risk analysis. Six different scenarios were created and analyzed using the software @Risk™ to measure the risk of introduction of bovine tuberculosis into this epidemiological compartment. The Mexican national program for control and eradication of bovine tuberculosis norm, regional prevalence on bovine tuberculosis, and current cultural practices in Tepalcatepec valley were considered for this analysis. The introduction of replacement heifers or sires into the farms, and the probability of the introduction of at least one infected animal was estimated. The least probable scenario for the introduction of tuberculosis into this compartment was the introduction of at least one infected animal, despite the prevalence of source herd, after applying tuberculin caudal fold test and cervical comparative test in parallel. Although some farmers are aware that the silvopastoral system is profitable, environmental friendly, and socially acceptable, initial investment appears to be the first barrier for adoption. Alternatives for funding SPS development are needed such as preferable interest rates, credit, and loans; notably, an accurate assessment of the costs for establishment of SPS should be more thoroughly studied. The initial three years of SPS implementation have the highest amount on investment; for those years, special attention should be placed on recording the contributions of timber and/or fruit to financial returns, since these products may be the key for offsetting the cost of SPS implementation Further research is needed to more accurately measure the economic, ecological, animal health, and human health impact of the silvopastoral model of farming in the tropics. An ample variety of species combinations, suitable for silvopastoral production, should be studied and different arrays proposed to encourage scaling up the model. Research funding is scarce; however, public awareness of the need for a change in production practices and the allure of environmental friendly-produced animal products can produce a market-driven change in these small-scale food production operations. This could engender greater research support from industry and government sources, as well as non-governmental organizations dedicated to promoting sustainable agricultural practices in a changing global environment.
Keywords: Mexico; risk analysis; system analysis; participatory epidemiology; bovine tuberculosis; silvopastoral